Affordances of musical instruments: Conceptual consideration - Tullberg, Markus (Frontiers in Psychology, 2022)
This article aims to contribute to a conceptualisation of affordances of musical instruments. The concept of affordances has been adapted by music researchers to some extent and due to various interests of the authors, there are many conflicting interpretations in the literature today. Still, the concept has the potential to be a powerful analytical tool, deployed to explore, describe and further develop the complex relationship between musician and musical instrument. However, in order for affordances to be used in such way, this particular field of study needs a definition that is both consistent and resilient enough to be meaningful across the study of different instruments. Furthermore, the concept of affordances does not come cheap. It enters the picture with strong ontological claims and thus prompts the researcher to be careful when merging it with other theoretical domains. A conceptualisation of affordances in relation to musical instruments must therefore be a stepwise project. Among the disputes surrounding affordances is whether they are to be taken as dispositional or relational. In this article, I argue for a relational interpretation. From this follows that the unit of analysis is the relationship and interaction between musician and instrument. The challenge is then how this interaction is to be defined. Based on the analysis of two empirical studies, and by combining Gibson’s ideas with enactivist theories, I propose the concept of sensorimotor relationship. This concept is taken as a key component in the proposed definition of affordances of musical instruments. My hope is that such conceptualisation can provide a path to further explorations on the experience of learning and playing musical instruments.